Analysis Of Financial Value With The Measurement Of Financial Ratios In Companies Jointed In The Multiple Industrial Sector (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study examines the impact caused by the ratio of loss to firm value in companies that are members of various industrial sectors. The movement between variables that occurs is one of the phenomena that occurs in the sector. The sample selected is as many as 13 companies using descriptive verification method. The results showed that the financial ratios used by measuring ROE, DER and SIZE had no effect on Firm Value as measured by PBV.